Advancing stroke diagnosis and management through nuclear medicine: a systematic review of clinical trials - Azhari, Hala F. (Frontiers in Medicine, 2024)
Introduction Despite advancements in stroke care, challenges persist in timely triage and treatment initiation to prevent the burden of stroke-related disabilities. Although nuclear medicine has shown promise, no imaging technique has yet provided a sufficiently rapid, precise, and cost-effective approach to routine stroke management. This study aims to review the clinical application of nuclear medicine in stroke diagnosis and treatment. Methods A systematic search of the Cochrane, EU Clinical Trials Register, ISRCTN, the International Stroke Trial, and the ClinicalTrials.gov database was conducted to find all registered trials reporting nuclear medicine’s clinical applications in stroke up to June 07, 2024. Results Among the 220 screened trials, 51 (36 interventional; 15 observational) met the eligibility criteria. Participants were older than 18 years old, with only six studies including pediatric under 17 years old, with a total of 11,262 stroke (9,232 ischemic; 2,030 haemorrhagic) participants. The bias risk varied across trials but remained mostly low to moderate. Discussion The review highlighted nuclear medicine’s significant contributions to stroke diagnosis and management, notably through mobile stroke units, pre-hospital acute stroke magnetic resonance image (MRI) based biomarkers, and MRI-based stroke mechanisms for 4D flow nuclear imaging. These advancements have generally reduced treatment delays and enhance clinical outcomes post-stroke. Specifically, radiopharmaceutical radiotracers can effectively discriminate between strokes and mimics, particularly in high-risk patients. Integrating novel positron emission tomography (PET) radiotracer 18F glycoprotein 1 and radionuclide angiography may improve sensitivity and specificity in thrombi detection for decisions regarding stenting or carotid endarterectomy, and the single-photon emission computed tomography and PET integration with ferumoxytol radiotracer-enhanced MRI enables functional imaging for evaluating cerebral perfusion, metabolic activity, and neuroinflammatory markers post-stroke. Overall, the integration of nuclear medicine into multimodal imaging equipment like computed-tomography PET and MRI-PET offers a more comprehensive picture of the brain. Nevertheless, further research is needed on novel stroke imaging techniques and standardization across stroke centers for optimal performance. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024541680, identifier PROSPERO CRD(42024541680).